UNIT 3.13 Clustal Omega. Issue 1 (12th December 2014) - Sievers, Fabian; Higgins, Desmond G.
Abstract : Clustal Omega is a package for making multiple sequence alignments of amino acid or nucleotide sequences, quickly and accurately. It is a complete upgrade and rewrite of earlier Clustal programs. This unit describes how to run Clustal Omega interactively from a command line, although it can also be run online from several sites. The unit describes a basic protocol for taking a set of unaligned sequences and producing a full alignment. There are also protocols for using an external HMM or iteration to help improve an alignment. © 2014 by John Wiley & Sons, Inc.